Upaya Pengendalian Mutu Produk Menggunakan Metode Statistical Process Control Dan 5W+1H Di PT. Mitra Rekatama Mandiri - Mella Wulandari; Widya Setiafindari (Pusat Riset dan Inovasi Nasional, 2023)
PT Mitra Rekatama Mandiri is an industrial foundry that makes metal products. The problem that occurs in the company is related to the quality of products that are still experiencing defects with the percentage of defects reaching 5.6% during February-March 2023. The research conducted aims to identify the dominating errors in the fabrication process, determine the factors that cause product defects. The methods applied are Statistical Process Control and 5W + 1H to be able to analyze problems related to product quality control. Based on the results of the study, there were 3 types of defects, namely 52% lossal defects, 30% porous, and 17% lossal defects. The results of the fishbone diagram are known factors that cause defects, namely human factors, methods, materials, machines.